Overexpression of the chloroplastic 2-oxoglutarate/malate transporter disturbs carbon and nitrogen homeostasis in rice. (25th July 2020) - Zamani-Nour, Shirin; Lin, Hsiang-Chun; Walker, Berkley J; Mettler-Altmann, Tabea; Khoshravesh, Roxana; Karki, Shanta; Bagunu, Efren; Sage, Tammy L; Quick, W Paul; Weber, Andreas P M
Abstract : Solute transport across the chloroplast envelope is controlled by metabolite concentration gradients and transporter abundance. Overexpression of an envelope dicarboxylate transporter causes a pronounced metabolic phenotype, indicating that transporter abundance directly affects metabolism. Abstract: The chloroplastic 2-oxaloacetate (OAA)/malate transporter (OMT1 or DiT1) takes part in the malate valve that protects chloroplasts from excessive redox poise through export of malate and import of OAA. Together with the glutamate/malate transporter (DCT1 or DiT2), it connects carbon with nitrogen assimilation, by providing 2-oxoglutarate for the GS/GOGAT (glutamine synthetase/glutamate synthase) reaction and exporting glutamate to the cytoplasm. OMT1 further plays a prominent role in C4 photosynthesis: OAA resulting from phosphoenolpyruvate carboxylation is imported into the chloroplast, reduced to malate by plastidic NADP-malate dehydrogenase, and then exported for transport to bundle sheath cells. Both transport steps are catalyzed by OMT1, at the rate of net carbon assimilation. To engineer C4 photosynthesis into C3 crops, OMT1 must be expressed in high amounts on top of core C4 metabolic enzymes. We report here high-level expression of ZmOMT1 from maize in rice ( Oryza sativa ssp. indica IR64). Increased activity of the transporter in transgenic rice was confirmed by reconstitution of transporter activity into proteoliposomes. Unexpectedly, overexpression of ZmOMT1 in rice negatively affected growth, CO2 assimilation rate, total free amino acid content, tricarboxylic acid cycle metabolites, as well as sucrose and starch contents. Accumulation of high amounts of aspartate and the impaired growth phenotype of OMT1 rice lines could be suppressed by simultaneous overexpression of ZmDiT2 . Implications for engineering C4 rice are discussed.